Cultroribula bicultrata - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Cultroribula bicultrata (Berlese, 1905) Material – One specimen in Taşköprü forest, Karadedeoğlu Village, N 41° 23′ 08.05′′, E 34° 25′ 07.52′′, alt. = 1126 m, 24 July 2018, tree bark and debris of P. Nigra; one specimen in Çamkonak Forest Processing Area, Daday forest. N 41° 23′ 55.18′′, E 33° 13′ 09.44′′, alt. = 1136 m, 30 May 2018, tree bark and debris of P. nigra. Previous record in Turkey – Kocaeli (Baran and Merve 2019; Yaça and Baran 2019). Global distribution – Holarctic. Ecology – Forest soils.

Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 260, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444
Keywords: Arthropoda; Cultroribula; Cultroribula bicultrata; Arachnida; Astegistidae; Animalia; Biodiversity; Sarcoptiformes; Taxonomy; 2. Zero hunger; 15. Life on land